Caspase 3 Targeted Cargo Delivery in Apoptotic Cells Using Capped Mesoporous Silica Nanoparticles. Issue 44 (10th September 2015) - de la Torre, Cristina; Mondragón, Laura; Coll, Carmen; García‐Fernández, Alba; Sancenón, Félix; Martínez‐Máñez, Ramón; Amorós, Pedro; Pérez‐Payá, Enrique; Orzáez, Mar
Abstract Excessive apoptotic cell death is at the origin of several pathologies, such as degenerative disorders, stroke or ischemia‐reperfusion damage. In this context, strategies to improve inhibition of apoptosis and other types of cell death are of interest and may represent a pharmacological opportunity for the treatment of cell‐death‐related disorders. In this scenario new peptide‐containing delivery systems (solids S1‐P1 and S1‐P2) are described based on mesoporous silica nanoparticles (MSNs) loaded with a dye and capped with the KKGDEVDKKARDEVDK (P1) peptide that contains two repeats of the DEVD target sequence that are selectively hydrolyzed by caspase 3 (C3). This enzyme plays a central role in the execution‐phase of apoptosis. HeLa cells electroporated with S1–P1 are able to deliver the cargo in the presence of staurosporin (STS), which induces apoptosis with the consequent activation of the cytoplasmic C3 enzyme. Moreover, the nanoparticles S1‐P2, containing both a cell‐penetrating TAT peptide and P1 also entered in HeLa cells and delivered the cargo preferentially in cells treated with the apoptosis inducer cisplatin.